The knowledge of zakat in business among Muslim entrepreneur in Kelantan - Amirah Mohammad Ismail; Anis Amirah Ali; Dinni Qistina Joha; Mohamad Adam Ab Halim (2022)
This study related to the knowledge of zakat in business among Muslim entrepreneurs in Kelantan is the first study conducted by researchers. The process of data entry, analysis tests and findings have also been done according to the desired process and the results obtained are seen to meet the questions formed. In fact, the findings have also been able to answer all research questions and research objectives. The results of the studies and discussions that have been presented in this study clearly show that the level of knowledge about zakat in business among Muslim entrepreneurs in Kelantan is at a moderate level. However, this study has limitations that should be considered where; this study uses a small sample size causing the results to be less accurate. The study sample is also limited to Muslim entrepreneurs in Kelantan only and does not represent all Muslim entrepreneurs in Malaysia. However, the results of this study can be utilized by various parties to increase the knowledge of Muslim entrepreneurs about zakat in business.